Well-defined palladium N-heterocyclic carbene complexes bearing CF3 moiety: Synthesis, characterization, crystal structure, direct C4-arylation of 3,5-dimethylisoxazole and antioxidant activity - Kalcik, Aysegul; Kaloglu, Nazan; Keser, Serhat; Sahin, Zarife Sibel; Dusunceli, Serpil Demir (Elsevier Science Sa, 2026)
A series of palladium N-heterocyclic carbene (NHC) complexes including trans-[Pd(NHC)Br2L] (L = C5H5N, 3-ClC5H4N, and N-methylimidazole) and [Pd(NHC)2Br2] have been prepared from {1-(benzyl)-3-(3,5-(bis(tri-fluoromethyl)benzyl)benzimidazolium bromide}. The structures of these new compounds were confirmed by NMR, FT-IR, and elemental analyses. The crystal structures of the dibromo-[1-(benzyl)-3-(3,5-(bis(tri-fluoromethyl)benzyl)benzimidazole-2-ylidene]-(pyridine)-palladium(II) and dibromo-[1-(benzyl)-3-(3,5-(bis (trifluoromethyl)benzyl)benzimidazole-2-ylidene]-(N-methylimidazole)-palladium(II) were determined by single-crystal X-ray diffraction. Palladium complexes were developed as efficient pre-catalysts for direct C4-arylation of 3,5-dimethylisoxazole and aryl bromides. Biological efficiency of trans-[Pd(NHC)Br2L]was evaluated by antioxidant activities like ABTS, OH and DPPH radical scavenging activity assays.
Keywords: Palladium complex; N -Heterocyclic carbene; Direct C4-arylation; Isoxazole; Antioxidant activity